Transport Across Chloroplast Membranes: Optimizing Photosynthesis for Adverse Environmental Conditions - Pottosin, Igor; Shabala, Sergey (Molecular plant, 2016)
Chloroplasts are central to solar light harvesting and photosynthesis. Optimal chloroplast functioning is vitally dependent on a very intensive traffic of metabolites and ions between the cytosol and stroma, and should be attuned for adverse environmental conditions. This is achieved by an orchestrated regulation of a variety of transport systems located at chloroplast membranes such as porines, solute channels, ion-specific cation and anion channels, and various primary and secondary active transport systems. In this review we describe the molecular nature and functional properties of the inner and outer envelope and thylakoid membrane channels and transporters. We then discuss how their orchestrated regulation affects thylakoid structure, electron transport and excitation energy transfer, proton-motive force partition, ion homeostasis, stromal pH regulation, and volume regulation. We link the activity of key cation and anion transport systems with stress-specific signaling processes in chloroplasts, and discuss how these signals interact with the signals generated in other organelles to optimize the cell performance, with a special emphasis on Ca2+ and reactive oxygen species signaling. This review describes the molecular nature and functional properties of the inner and outer chloroplast envelope and thylakoid membrane channels and transporters, and discusses how their orchestrated regulation affects thylakoid structure, electron transport and excitation energy transfer, proton-motive force partition, ion homeostasis, stromal pH regulation, and volume regulation. Stress-specific signaling processes in chloroplasts are discussed, with special emphasis on Ca2+ and ROS signaling.